The Effect of the Talking Flashcards Device in Enhancing Students’ Memory Retention in English Learning - Samman, Yulianti; Syahrir, Syahrir; Aliah, Husnani (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aimed to examine the effect of the Talking Flashcards Device on students’ memory retention in English vocabulary learning at SDN 2 Nanggala. The research employed a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. The participants consisted of 45 elementary students, including 21 fourth-grade and 24 fifth-grade students. The experimental group was taught using the Talking Flashcards Device, while the control group received conventional instruction. The instruments used were pre-test, post-test, and follow-up test consisting of 20 multiple-choice items designed to measure students’ vocabulary retention. Data were analyzed using descriptive statistics, Independent Samples t-test, Paired Samples t-test, and Repeated Measures ANOVA through SPSS version 20. The findings revealed that there was no significant difference between the experimental and control groups in the pre-test (p > 0.05), indicating comparable initial abilities. However, significant differences were found in both post-test and follow-up test results (p < 0.05), demonstrating the effectiveness of the treatment. The mean scores increased from 9.82 in the pre-test to 13.09 in the post-test and further improved to 15.27 in the follow-up test. The paired samples t-test showed a statistically significant improvement (p < 0.001) with a very large effect size (Cohen’s d = 1.327). In addition, the Repeated Measures ANOVA confirmed a significant effect of time, indicating consistent improvement across all testing stages. These results suggest that the Talking Flashcards Device effectively enhances both short-term vocabulary mastery and long-term memory retention. The integration of visual and auditory elements supports stronger encoding and retrieval processes, in line with Dual Coding Theory. Therefore, this device can be recommended as an innovative and effective instructional medium for improving vocabulary learning, particularly for elementary students in rural EFL contexts